The influence of guided inquiry learning models on science process skills and student learning outcomes on chemical equilibrium material - Anna Juniar; Indra Amparodman Sianipar (Jurnal Pendidikan Kimia (JPKim), 2022)
This study aims to determine the effect of the guided inquiry model on improving science process skills and learning outcomes of its correlation in chemistry. This research was conducted at SMA Negeri 1 Siantar Narumonda. The sample in this study consisted of two classes, each of which consisted of 30 students who were taught using guided and conventional inquiry learning models. The instruments used were multiple choice tests (Learning Outcomes), essay tests (Science Process Skills), student worksheets, and observation sheets on the implementation of science process skills. The results of the analysis obtained that the average gain of student learning outcomes who were taught using the guided inquiry learning model (0.789) was different from the conventional model (0.698) and the average gain of science process skills using the guided inquiry model (0.858) was different from the use of conventional learning models (0.789). Hypothesis testing using a two-party t-test for student learning outcomes and science process skills was obtained at 4.465 > 2.00172 and 7.051 > 2.0172. Thus, it was found that there was an influence of the guided inquiry learning model on student learning outcomes and science process skills. The correlation test showed that there was a correlation between learning outcomes and students' science process skills with an r count of 0.525 > 0.361 with a contribution of 27%.Keywords:Chemical equilibrium, Guided inquiry, Learning outcomes, Science process skills